Successful Treatment of Hemifacial Myokymia and Dystonia Associated to Linear Scleroderma “En Coup de Sabre” with Repeated Botox Injections - Carlos A. Cañas; Jorge L. Orozco; Andrea Caicedo Paredes; Fabio Bonilla-Abadía (Case Reports in Medicine)
Linear scleroderma “en coup de sabre” (LSCS) is a form of localized scleroderma presents as band-like sclerotic lesions of the frontoparietal area. It has been reported in association with diverse neurological manifestations like seizures, migraine, neuromyotonia, dystonia and abnormalities in MRI and CT studies as cerebral atrophy, white matter lesions, intraparenchymal calcification, meningeocortical alterations, and skull atrophy. We describe a patient with LSCS associated with two abnormal movements: permanent myokimia of right masseter muscle and recurrent spasmodic retraction of right cigomatic and depressor labii inferioris muscles. He was initially treated with methotrexate and steroids without response, so later on he underwent repeated Botox injections with remarkable improvement.